Web design: guia de produção e análise - Almeida, Cândida (2009)
"Web Design: production and analysis guide" is a scientific research that intends to investigare the context of development and the processes of website production for the WWW (World Wide Web). In this thesis, the term production is understood as the realization of a wide range of procedures that go from the creative conception, passing through structural organization, visual development, tools implementation, to effectuation of the many kinds of relationships between online hypermedias and the interactors. Based on Peircean Semiotics concepts and the General Systems Theory, this present research has the objective of providing an oriented guide to production and analysis of online-based projects. Besides gathering an extensivetheoretical data to clarify the steps involved in these types of productions, this thesis also developed a theoretical rarionale that indicares ways and conducrs for producers to develop projecrs thar are eHecrive from rhe communicarive poinr of view. With phenomenological emphasis on rhis type of development invesrigation, we consider the web design production as a systemic process, composed of a wide range of different signs, conducred by normative ideas, and developed from specific reasonings. Throughour the rhesis, we explain the rheoretical rationale through several analysis applied ro exisring websites. This implies that the enrire rarionale promptly leads to rhe empirical demonstrarion of irs applicability and eHiciency as an importanr subsrratum for a guide to production and analysis of rhe hypermediatic forms of interpersonal communlcarlon